Evaluation of the Outcome of Patients with Papillary Thyroid Carcinoma with Surgical Intervention (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background : Papillary Thyroid Carcinoma (PTC) is the most common form of well differentiated thyroid cancer, and constitutes 1% of all solid tissue cancers with a female predominance and surgical intervention helps in removal of the cancer.Methods: A retrospective data analysis was done among 70 papillary thyroid carcinoma patients who had undergone radical thyroidectomy with or without selective lymph node excision in the Department of Breast and Thyroid Surgery at Shandong Provincial Hospital from 2005 to 2012.Results: The study showed a female predominance with a mean age 43.81years. 71.4% cases presented with lymphadenopathy and out of 70 patients, 16 had previous thyroid hormone dysfunction. Radical Thyroidectomy with selected lymph node excision was done in 77.1% cases and the rest had undergone only Radical Thyroidectomy. 44.3% of the tumor was